Pengaruh Pretreatment pada Fermentasi Bioetanol Generasi Kedua dari Serat Buah Kelapa Sawit - ojsadmin; Adrianto Ahmad; Idral Amri; Wida Sri Wani (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2020)
Indonesia is a country with a growing human population, causing the need of energy also increases. Bioethanol has been widely used in transportation as a fuel that is increasingly reduced. Palm fruit fiber has a high enough potential to be developed into an alternative energy source, namely bioethanol because of its high lignocellulosic content. The purpose of this study was to determine the composition of sulfuric acid in the hydrolysis process, determine the initial sugar composition of the bioethanol produced, and determine the optimal processing time for the formation of bioethanol in the Hydrolysis and Separate Fermentation (SHF) method. The stages in this study were the hydrolysis of palm fruit fiber using H2SO4 with variations of 1M, 2M, and 3M for 3 hours at 100 oC. The fermentation process is carried out with variations in time for 24 hours, 48 hours, 72 hours, 96 hours and 120 hours. The results showed that in the hydrolysis process the optimum H2SO4 concentration of 3M produced a sugar concentration of 87.83 gr/L. The fermentation process obtained an optimal fermentation time of 96 hours with a bioethanol concentration of 31.57 g / L. The greater the initial concentration and the longer time fermentation, the more bioethanol is obtained at optimal times.